Factors determining residential locations of employees in the Kuala Lumpur conurbation of Malaysia - Mohit, Mohammad Abdul; Asmawi, M. Zainora (Research Management Centre, IIUM, Kuala Lumpur, 2009)
Urbanization in Malaysia has grown rapidly especially during the last two decades whereby the rate of urbanization has increased from 53.4% to 65.4% between 1991 and 2000 Current rate of urbanization in Malaysia is 63% and it is projected that the rate will be 75% by the year 2020. Although there are many urban centres in Malaysia but it is expected that the increase in urban population will mostly occur in larger urban conurbations around Kuala Lumpur, Georgetown, Johor Bahru and Kuantan. Therefore, a study of the factors determining urban land use through the residential location choice of those employed within the urban areas in the conurbations appear to be important in determining the future physical forms or urban spatial structures of those conurbations. Three objectives were set for this study – (a) to investigate the socio-economic, housing and commute characteristics of the employees of KL City; (b) to explore the relationships among social-economic, housing and commute characteristics of the employees of KL City; and (c) to examine the nature and the significance of the relationships between the identified factors and the residential locations of KL City service sector employees. Based on a questionnaire survey covering 529 employees drawn from a cross-section of six sub-sectors of the service sector, the study found that none of the four socio-economic factors affected or influenced residential location. All the four housing characteristics – house type, house size, number of bedrooms and toilets, commute cost as percentage of income, were found to exert influence on residential location. The residential pattern of homewoners were more dispersed than the renters. Single employed respondents’ mean commute distance was less than multiple employed respondents. The workplace of primary employment was less than secondary employment. The mean distance between a respondent’s home and workplace was higher than the mean distance between the respondent’s home and school. It thus appears that the residential location chioce of the employees of Kuala Lumpur provides supports more to the access versus space trade-off model developed by the location theorists.